ON DORCATHERIUM NAGRII (TRAGULIDAE, MAMMALIA) - WITH A REVIEW OF SIWALIK TRAGULIDS (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1992)
Well-preserved maxillary and mandibular fragments of Dorcatherium nagrii described in this paper from the Middle Siwaliks of Haritalyangar (India) provide a more complete diagnosis of D. nagrii. On the basis of detailed comparison, statistical analysis and review of variors Dorcatherium species from Siwaliks, changes in the specific affiliations of some of the Dorcatherium material described earlier are suggested. The estimated body weight of Siwalik dorcatheres ranges from approximately 4 kg to 41 kg.
Keywords: Mammals; Dorcatheres; Systematic review; Siwalik; India; Neogene